RELATIONSHIP BETWEEN EDUCATION AND EXISTING HOUSING CONDITIONS OF ELDERLY PEOPLE - R. UNESHA FAREQ*, T. NEERAJA; V. PRASUNA (The Journal of Research ANGRAU, 2021)
The study aimed to understand the relationship between education andexisting housing conditions of the elderly. The elderly women in the age group of sixty and above who were able to carry out their daily chores were selected as sample. The standard design guidelines evolved through research by various Government and Non-government organizations and researchers served as a base to identify the existing housing conditions of the elderly people.The findings of the study revealed that education of the respondent was found to be a factor that determined the design of the communication systems in the home in the residences.Comparatively, highly-educated elderly respondents i.e. who completed graduation degree or above graduationwere found having technical knowledge and taking the advantage of technology concerning communication systems in their homes.